Integrative Proteomics and Genomics Identify Novel Biomarkers and Therapeutic Targets in Vitiligo via Mendelian Randomization - Chenjue Yan; Ling Jiang; Yibo Hu; Ting You; Jing Chen; Songjiang Wu (Dermatology and Therapy)
Abstract Introduction Given that the proteome is a major source of therapeutic targets, we conducted a proteome-wide Mendelian randomization (MR) combined with transcriptome sequencing analysis to identify candidate protein markers and therapeutic targets for vitiligo. Methods Based on protein quantitative trait loci (pQTLs) and genetic associations with vitiligo obtained from the European Bioinformatics Institute (EBI) database (60 vitiligo cases and 402,672 controls), and the UK Biobank (95 vitiligo cases and 337,064 controls), bidirectional MR and colocalization analyses identified genetically predicted levels of nine proteins collectively linked to vitiligo risk. Based on the RNA-seq data and single-cell RNA-seq data of vitiligo, bioinformatics analysis and model prediction of genes associated with vitiligo progression evaluated the relationship between candidate core proteins and the development of vitiligo. Results Four proteins (KLF4, MYL4, TNFRSF13C, TNFSF13B) were associated with lower vitiligo risk, while five proteins (ALPI, CDH1, ITGB1, SERPINH1, TNFSF10) were linked to higher risk. Of these, three proteins (KLF4, TNFRSF13C, and TNFSF10) were high priority with the most convincing evidence. Bioinformatics analysis and model prediction of genes associated with vitiligo progression showed these three protein-coding genes were significantly associated with vitiligo occurrence, and their functions were related to cell cycle, apoptosis, oxidative stress, inflammatory response, and immune infiltration. Mechanistically, the expression of these key candidate molecules was regulated by various miRNAs and transcription factors. The druggability assessment and molecular docking identified some drugs targeting these proteins, such as APTO-2535 and butyric acid. Conclusion KLF4, TNFRSF13C, and TNFSF10 may be involved in regulating the occurrence and development of vitiligo, providing potential targets for improving the diagnosis and treatment of vitiligo. Graphical Abstract